Statistics for the social sciences. 3rd ed. - Sirkin, Mark R. (London, 2006)
"Do your students lack confidence in their ability to handle quantitative work? Do they get confused about how to enter statistical data on SAS, SPSS, and Excel programs? The new Third Edition of the bestselling Statistics for the Social Sciences is the solution to these dilemmas!